Konsep Soul Share Pada Pemasaran Syariah Baitul Maal Wat Tamwil (BMT) Di Banten - Mulyadi Mulyadi (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2016)
The purpose of this study was to determine and analyze in depth the concept of soul share the marketing of Shariah BMT in Banten. The method used is descriptive qualitative with phenomenological approach. Phenomenological study tries to explain or reveal the meaning of a concept or phenomenon based on the experience of consciousness that occurs in some individuals. The samples were consist of 6 BMT in the province of Banten, namely: BMT Great Mosque of Serang, Pandeglang BMT BMT Darul Falah EL-STIEM Kota Tangerang. BMT Al-Qoryah Anyer Serang regency, BMT Bina Tijaroh Cilegon and BMT La-Syakka Lebak. The analysis technique used is to use interactive model. In the analysis model, there are three (3) components of the analysis, namely: data reduction, data display and conclusion. The results of this study revealed that the concept of soul share in marketing of Shariah BMT in Banten is: Honesty as a capital BMT in getting the trust of the public, and transparency. With customers increasingly believe in the sincerity of BMT, BMT at the boarding school does not have a human resources professional, because its organizer doubles as a cleric and lectures, while at BMT has been a professional market. BMT friendship is a strategy to mantain customers satisfaction and keep in touch with customers.